Word cloud of online hotel reviews in Thailand for customers’ satisfaction analysis - Vimolboon Cherapanukorn (2018)
© 2018 Pushpa Publishing House, Allahabad, India. This study intends to examine the satisfaction and dissatisfaction of hotel customers by using a word cloud approach to evaluate online reviews. Online comments of 9,709 hotel guests were collected from TripAdvisor.com for 30 hotels in three cities of Thailand. The results revealed some common features that are identified in both these kinds of customer reviews. Therefore, this article suggests a clear managerial implication pertaining to understanding of hotel guest satisfaction level via the utilization of world cloud technique through online platforms.